“You’re just constantly on alert”: Women and Gender-Diverse People’s Experiences of Sexual Violence on Public Transport - Ison, Jessica (Journal of interpersonal violence, 2023)
Sexual violence is a public health issue that can be experienced across the life course. Public transport is a key site of sexual violence and harassment experienced by women and gender-diverse people in Australia, although victim-survivor voices have rarely been sought in addressing this issue. Through in-depth qualitative interviews with 41 diverse female and gender-diverse victim-survivors who were staff or students at two Australian universities, we sought to understand their experiences of sexual violence and harassment on public transport. We found that women and gender-diverse people, while often reporting on a significant experience of sexual violence or harassment on public transport, also had other, “everyday” experiences across their life course that impacted how they traveled and their confidence in the world. Overall, we argue that the significant impact of sexual violence and harassment on public transport should be addressed through targeting public transport as a key site for primary prevention of sexual violence and harassment.